Geëngageerde kunst. - Kotte, Wouter (Utrecht : Hedendaagse Kunst Utrecht, 1982)
Acconci, Vito ; Arroyo, Eduardo ; Errò ; Flora, Paul ; Gerritsen, W ; Hrdlicka, Alfred ; Immendorff, Jörg ; Kennard, Peter ; Kienholz, Edward ; Klasen, Peter ; Marcos, Alejandro ; Mc Geoch, Brian ; van Rensen, Kees ; Rubin, Harold ; Scott, Maureen ; Tryard, Keith ; Waller, Jürgen ; Wickrama Sinha, Marlini
Geëngageerde kunst, Hedendaagse Kunst, Utrecht
Nederlands
kunstcatalogus